Ex-post impact assessment review of the Regional Network on AIDS, Livelihoods, and Food Security (RENEWAL) - Frankenberger, Timothy R.; Nelson, Suzanne (International Food Policy Research Institute, 2011)
This report assesses the impact of RENEWAL activities from 2000 to 2010 and is based on a review of products resulting from RENEWAL activities (such as books, policy briefs, workshop summaries, reports, and discussion papers), stakeholder perceptions of RENEWAL products and activities, and national policy or programming changes resulting from RENEWAL-supported action research, capacity strengthening efforts, and policy communications.